Economic and financial viability of wheat production in Cameroon - Farida, Adama; Leonard, Ngonkeu Mangaptche Eddy; Gankou, Jean Marie (Journal of Scientific Agriculture, 2025)
This study evaluated the economic and financial profitability of wheat production in Cameroon using data from 300 individuals in Adamawa, North-West, and West regions. Key factors influencing profitability were identified through correlation heatmaps, pair-plot diagrams, and modeling algorithms (Generalized Least Squares, Random Forest, and Least Absolute Shrinkage and Selection Operator). Positive factors included production volume, packaging, and transportation costs, while negative factors included production workforce, experience, and fertilizer costs. The net margin for wheat production was positive at 76,691,000 FCFA, but financial profitability was low, with an import-to-export ratio of 0.16. The study highlights the need to enhance wheat production to reduce importation.